2016
DOI: 10.1134/s0012496616010087
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic constituents of the extreme head turn of Strix aluco estimated by means of CT-scanning

Abstract: To analyze extreme sideways turn of the head in owls, a total fresh specimen of Strix aluco was frozen in respective posture and CT-scanned. The maximum turn to one side was found to be 360°, provided that the head is drawn into the shoulders. 160° of this full turn are ensured by the neck axial rotation (this includes ~90° twist of the head relative to epistropheus and, posterior to it, less than 15° per every cervical joint), and the rest 200° are ensured by combination of dorsal and lateral flexion. The 15°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 3 publications
0
32
0
Order By: Relevance
“…Neck rotations of up to 180°are also known from other birds (Dzemski & Christian, 2007), but a 270°neck rotation capability is considered outstanding (Grytsyshina et al 2016). de Kok-Mercado et al (2013) found the arterial canals of the cervical vertebrae of owls to be much wider than the arteries crossing them.…”
Section: Comparison With Morphology Of Bird Neckmentioning
confidence: 99%
See 1 more Smart Citation
“…Neck rotations of up to 180°are also known from other birds (Dzemski & Christian, 2007), but a 270°neck rotation capability is considered outstanding (Grytsyshina et al 2016). de Kok-Mercado et al (2013) found the arterial canals of the cervical vertebrae of owls to be much wider than the arteries crossing them.…”
Section: Comparison With Morphology Of Bird Neckmentioning
confidence: 99%
“…For example, the beak has to reach every feather at the body to allow appropriate plumage care (Stark, 1979). Owls have an outstanding headrotation capability (Grytsyshina et al 2016). This makes owls an interesting study case for neck mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of just FE and ABAD (Gishlick, 2001;Carpenter, 2002;Senter & Robins, 2005;Carpenter & Wilson, 2008) are incomplete and ambiguous if LAR is not measured. A few studies have quantified ROM about all three rotational DoFs (3-DoFs) in joints with more complex shapes (Chan, 2007;Pierce et al 2012;Hutson & Hutson, 2013;Arnold et al 2014;Grytsyshina et al 2016), but the analysis, interpretation, and presentation of these data are difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, avian necks are typically considered to have substantial mobility in dorsoventral flexion and lateroflexion, while the heterocoelous centra are accepted to preclude significant axial rotation (torsion) in vertebrae caudal to the atlas/axis [23, 26–28]. Quantification of avian cervical joint range of motion (ROM) has frequently been performed passively via hand-manipulation of cadaveric material with and without soft-tissues intact [17, 26, 27, 29–35]; however, a few studies have documented in vivo neck motion (e.g. [17, 32]).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have quantified lateroflexion in addition to, and independently of, dorsoventral flexion [26, 33]. Only three studies have attempted to reconstruct bird neck movements in three dimensions (specifically in owls [35, 39, 40]), with the potential to quantify all three rotational degrees of freedom simultaneously, including axial rotation. Such data are critical for understanding joint function, as musculoskeletal movements incorporate motion around multiple degrees of freedom simultaneously (e.g.…”
Section: Introductionmentioning
confidence: 99%